ANALISIS BIAYA DAN STRATEGI PENGEMBANGAN OBJEK WISATA MATANG KALADAN, KABUPATEN BANJAR - Mayske Ellora Anggraeni; Muhammad Helmi; Fonny Rianawati (Jurnal Sylva Scienteae, 2023)
Matang Kaladan Tourist Attractions one of the tourist destinations has an attraction in South Kalimantan. Matang Kaladan Tourism presents a view above the peak, so that it attracts visitors or tourists to come, and there are facilities in the form of photo spots that allow management at the Kaladan Matang Tourism location. The purpose of this study (1) analyzes management costs and revenues obtained from 2019-2021, (2) analyzes tourism development through SWOT methods and determines its development strategy. The methods used in this research cost analysis and SWOT. The results of the analysis of the cost of managing Kaladan Mature Tourist Attractions show the value of ratio = 1 in 2019 and 2020, and in 2021 shows the value of the ratio>1 "profitable business". SWOT analysis through quantitative approaches is worth x = 2.00 and y = 2.00. SWOT analysis through qualitative approach SO = 10.08, WO = 1.92, ST = 2.8, WT = (-6.08). Based on these values, Kaladan Mature Tourist Attractions from the cost analysis in 2019 and 2020 were declared "not profitable, but not disadvantaged" in the sense of "breakeven", while 2021 was declared "profitable business" in the sense of "feasible". SWOT analysis of x and y values (2.00, 2.00) the position of the attraction that shows that the position of the object is in Quadrant I, this is in a quantitative approach using so strategies. SWOT analysis through a qualitative approach using so, WO, ST, WT strategiesSelatan. Wisata Matang Kaladan menyajikan pemandangan diatas puncak, sehingga menarik pengunjung atau wisatawan berdatangan, serta terdapat fasilitas berupa spot foto yang memungkinkan adanya pengelolaan di lokasi Wisata Matang Kaladan. Tujuan dari penelitian ini (1) menganalisis biaya pengelolaan serta pendapatan yang diperoleh dari tahun 2019-2021, (2) menganalisis pengembangan wisata melalui metode SWOT serta menentukan strategi pengembangannya. Metode yang digunakan dalam penelitian ini Analisis Biaya dan SWOT. Hasil dari analisis biaya pengelolaan Objek Wisata Matang Kaladan menunjukkan nilai rasio=1 pada tahun 2019 dan 2020, serta tahun 2021 menunjukkan nilai rasio>1 “usaha menguntungkan”. Analisis SWOT melalui pendekatan kuantitatif bernilai x= 2,00 dan y= 2,00. Analisis SWOT melalui pendekatan kualitatif SO = 10,08 ,WO = 1,92 ,ST = 2,8 ,WT = (-6,08). Berdasarkan nilai tersebut Objek Wisata Matang Kaladan dari analisis biaya tahun 2019 dan 2020 dinyatakan “tidak untung, namun tidak dirugikan” dalam arti “impas”, sedangkan 2021 dinyatakan “usaha menguntungkan” dalam arti “layak”. Analisis SWOT nilai x dan y (2.00, 2.00) posisi objek wisata yang menunjukan bahwa posisi objek berada di Kuadran I, hal ini dalam pendekatan kuantitatif menggunakan strategi SO. Analisis SWOT melalui pendekatan kualitatif menggunakan strategi SO, WO, ST, WT